Analysis in Proceratophrys boiei genome illuminates the satellite DNA content in a frog from the Brazilian Atlantic forest - João Da Silva, Marcelo; Gazoni, Thiago; Haddad, Célio Fernando Baptista; Parise-Maltempi, Patricia Pasquali (Frontiers in Genetics, 2023)
Satellite DNAs (satDNAs) are one of the most abundant elements in genomes. Characterized as tandemly organized sequences that can be amplified into multiple copies, mainly in heterochromatic regions. The frog Proceratophrys boiei (2n = 22, ZZ♂/ZW♀) is found in the Brazilian Atlantic forest and has an atypical pattern of heterochromatin distribution when compared to other anuran amphibians, with large pericentromeric blocks on all chromosomes. In addition, females of P. boiei have a metacentric sex chromosome W showing heterochromatin in all chromosomal extension. In this work, we performed high-throughput genomic, bioinformatic, and cytogenetic analyses to characterize the satellite DNA content (satellitome) in P. boiei, mainly due to high amount of C-positive heterochromatin and the highly heterochromatic W sex chromosome. After all the analyses, it is remarkable that the satellitome of P. boiei is composed of a high number of satDNA families (226), making P. boiei the frog species with the highest number of satellites described so far. Consistent with the observation of large centromeric C-positive heterochromatin blocks, the genome of P. boiei is enriched with high copy number of repetitive DNAs, with total satDNA abundance comprising 16.87% of the genome. We successfully mapped via FISH the two most abundant repeats in the genome, PboSat01-176 and PboSat02-192, highlighting the presence of certain satDNAs sequences in strategic chromosomal regions (e.g. centromere and pericentromeric region), which leads to their participation in crucial processes for genomic organization and maintenance. Our study reveals a great diversity of satellite repeats that are driving genomic organization in this frog species. The characterization and approaches regarding satDNAs in this species of frog allowed the confirmation of some insights from satellite biology and a possible relationship with the evolution of sex chromosomes, especially in anuran amphibians, including P. boiei, for which data were not available.